The Political Dynamics of Southeast Asia and the Identity Transformation of ASEAN in Post-Cold War and Post-Economic Crisis 1997-1998 - Wahyu Rozzaqi Ginanjar; Ali Maksum (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
In general, regional integration takes the form of political economy initiatives focused on commercial interests to achieve broader socio-political and security goals. The Association of Southeast Asian Nations (ASEAN) is a regional organization in Southeast Asia. After the end of the Cold War, ASEAN underwent changes, especially in terms of norms, governance, and collective identity. This article aims to explain the institutional reform and transformation of ASEAN's identity as a regional organization after the end of Cold War era. Using Alexander Wendt's concept of Collective Identity, this article argues that the 1997-1998 crisis and political dynamics in Southeast Asia unraveled the weaknesses of ASEAN's traditional principles as a regional organization. This led to skepticism towards the credibility and function of ASEAN. In order to restore its image and credibility, ASEAN conducted institutional reform in some stages. The institutional reform started with conceptualizing shared ideas through the establishment of the ASEAN Community, which was then institutionalized in a set of norms through the ASEAN Charter. These institutional reforms gave birth to a common set of ideas and norms for the member states. These shared ideas and norms indicate the transformation of ASEAN's collective identity as a regional organization that is more in line with universal norms such as human rights, democracy, and good governance.